Novel abdomino-pelvic anomalies in Kagami-Ogata syndrome - Kelly Lamiman (Elsevier, 2021)
Kagami-Ogata syndrome (KOS) is a rare genomic imprinting disorder of chromosome 14 with characteristic facial features, a small, bell-shaped thorax, muscular hypotonia, and abdominal wall defects. We present a case of a kidney incarcerated in a posterolateral Bochdalek type congenital diaphragmatic hernia (CDH), intestinal malrotation and stage 2 rectocele in KOS. Successful repair of CDH and malrotation was achieved with Ladd's procedure, CDH repair, Nissen fundoplication and gastrostomy tube placement. She had no post-operative complications and is currently tolerating 100% enteral feeds. CDH, intestinal malrotation and rectocele have not been previously reported in KOS. Despite overall poor prognosis, KOS patients with CDH and malrotation can be repaired successfully with improvement in quality of life.